Damage evolution in the AlMg6 alloy during high and very high cycle fatigue (Fracture and Structural Integrity, 2019)
Paper presents the “in situ” method for determining of irreversible fatigue damage accumulation, based on the analysis of nonlinear manifestations of the feedback signal in a closed system of an ultrasonic fatigue system. During very high cycle (gigacycle) fatigue, the anomalies of the elastic properties of the material are appear, which leads to a nonlinearity effect in the amplitude of oscillations. This effect increases with the initiation and growth of fatigue cracks. The technology was applied to samples of AMG-6 alloy with preliminary dynamic deformation at various levels of average stress to determine the moment of initiation and growth of the fatigue crack in very high cycle fatigue regime. This method is applicable for the early detection of fatigue cracks both on the surface and inside the material under cyclic loading in the ultrasonic mode. On the basis of wide-range defining relations for a deformable solid body with mesoscopic defects, a mathematical model has been proposed that can adequately describe behavior of the material during fatigue failure. The results of mathematical modeling are in good agreement with the experimental data
Keywords: Damage accumulation; Scaling; High- and very high cycle fatigue; Mathematical modeling; Destruction; mesoscopic defects